The Effect of Rating and Lifestyle on the Purchase Decision of Skincare Products of Somethinc Brand on Gen Z in Medan City (Case Study on Shopee Marketplace) - Desma Erica Maryati Manik; Sri Rezeki; Tiffany Tiffany (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study aims to analyze the influence of ratings and lifestyle on purchasing decisions for Somethinc brand skincare products on generation Z in Medan City through the Shopee marketplace. The research method uses a quantitative approach with data collection through questionnaires distributed to 400 Gen Z respondents. The results of the analysis show that ratings have a significant influence on purchasing decisions, indicating that consumer assessments and reviews play an important role in building trust in products. In addition, the respondents' lifestyles are also proven to have a significant influence, where consumer lifestyles and preferences influence the choice of skincare products. Simultaneously, ratings and lifestyle together have a significant influence on purchasing decisions for Somethinc products. This study provides important insights for skincare business actors to improve product quality and marketing strategies that are in accordance with the characteristics and lifestyle of Gen Z, especially on the marketplace platform.